Analisis Swot Manajemen Risiko pada Pekerja Pabrik: Penelitian - Dhea Nadzwa Ashari; Amirah (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
This study aims to analyze the risks faced by factory workers using the SWOT analysis method. It uses a descriptive qualitative method with factory workers from Tegal Regency as the research subjects and uses primary data obtained through observation, interviews, and questionnaires as the data collection method or data source. From the results of observation, interviews, and questionnaire distribution, it was found that there are 12 risks faced by workers with risk identification, assessment, and control, as well as frequency levels ranging from very frequent to almost never occurring, with severity levels ranging from mild to severe. With the existence of risks and risk research, factory workers have ways to control risks, namely avoidance, control, containment, transfer, funding, reserves, and diversification to minimize losses.